Responsiveness of the Peyronie's Disease Questionnaire (PDQ). (9th February 2015) - Coyne, Karin S.; Currie, Brooke M.; Thompson, Christine L.; Smith, Ted M.
Abstract Introduction In order to reliably assess treatment effectiveness, patient‐reported outcome instruments must demonstrate adequate psychometric properties. Aim To assess the responsiveness of the Peyronie's Disease Questionnaire (PDQ) using data from two Phase 3 trials of collagenase clostridium histolyticum for Peyronie's disease (PD). Methods Both trials recruited adult males with PD who were in a stable relationship with a female partner for at least 3 months. Patients completed the PDQ, International Index of Erectile Function (IIEF), and a global assessment of PD (GAPD) questionnaire at baseline and Weeks 24 and 52. Anchor‐ and distribution‐based methods were used to evaluate the responsiveness of the PDQ. Main Outcome Measure Peyronie's Disease Questionnaire. Results The number of men available with baseline and Week 52 data was 267 for Study 1 and 270 for Study 2. The mean age was 58.0 for Study 1 and 57.4 for Study 2; the majority were white (95.2% and 97.3%, respectively). Mean PDQ subscale change scores from baseline to Week 52 for both studies ranged from −1.5 to −4.6 (P < 0.0001). In Study 1, effect sizes were moderate to large on the Psychological and Physical Symptoms (−0.56) and Symptom Bother subscales (−0.84). For patients with penile pain at baseline, the effect size was large (−1.05) for the Penile Pain subscale. Similar effect sizes were seen in Study 2. The Psychological and Physical Symptoms and Symptom Bother subscales significantly discriminated patient improvement ratings of GAPD and degree of penile curvature at Weeks 24 and 52. Conclusions The PDQ is highly responsive to change in men with PD. Coyne KS, Currie BM, Thompson CL, and Smith TM. Responsiveness of the Peyronie's Disease Questionnaire (PDQ). J Sex Med 2015;12:1072–1079.